Neutrophils—Important Communicators in Systemic Lupus Erythematosus and Antiphospholipid Syndrome - Wirestam, Lina; Arve, Sabine; Linge, Petrus; Bengtsson, Anders A. (Frontiers in Immunology, 2019)
Systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS) are two autoimmune diseases that can occur together or separately. Insights into the pathogenesis have revealed similarities, such as development of autoantibodies targeting subcellular antigens as well as a shared increased risk of cardiovascular morbidity, potentially due to mutual pathologic mechanisms. In this review, we will address the evidence implicating neutrophils in the pathogenesis of these conditions, highlighting their shared features. The neutrophil is the most abundant leukocyte, recognized for its role in infectious and inflammatory diseases, but dysregulation of neutrophil effector functions, including phagocytosis, oxidative burst and formation of neutrophil extracellular traps (NETs) may also contribute to an autoimmune process. The phenotype of neutrophils in SLE and APS differs from neutrophils of healthy individuals, where neutrophils in SLE and APS are activated and prone to aggregate. A specific subset of low-density neutrophils with different function compared to normal-density neutrophils can also be found within the peripheral blood mononuclear cell (PBMC) fraction after density gradient centrifugation of whole blood. Neutrophil phagocytosis is required for regular clearance of cell remnants and nuclear material. Reactive oxygen species (ROS) released by neutrophils during oxidative burst are important for immune suppression and impairment of ROS production is seen in SLE. NETs mediate pathology in both SLE and APS via several mechanisms, including exposure of autoantigens, priming of T-cells and activation of autoreactive B-cells. NETs are also involved in cardiovascular events by forming a pro-thrombotic scaffolding surface. Lastly, neutrophils communicate with other cells by producing cytokines, such as Interferon (IFN) -, and via direct cell-cell contact. Physiological neutrophil effector functions are necessary to prevent autoimmunity, but in SLE and APS these are altered.